Secondary battery and electric device

CN119731833APending Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202380061820.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing high-specific energy secondary batteries have limited their practical applications due to the strong activity and poor stability of lithium metal negative electrodes. The energy density of secondary batteries is insufficient, making it difficult to meet the wide application needs.

Method used

Using high-nickel ternary positive electrode material and high-silicon-based negative electrode active material, combining high-liquid-absorbing polymer and gel electrolyte, optimize the compaction density and electrolytic quality of the electrode sheet, reduce the external electrolyte of the bare core, improve the liquid retention capacity of the electrolyte, and enhance energy density.

Benefits of technology

The secondary battery with lithium-free metal negative electrode has high energy density and stability, meets a wide range of application needs, and improves the charging and discharging performance of the battery by optimizing the electrolyte distribution and electrode plate structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731833A_ABST
    Figure CN119731833A_ABST
Patent Text Reader

Abstract

Provided is a secondary battery including: a positive electrode plate having a positive electrode active material including LiaNixCoyMzO2, 0.2 < = a < = 1.2, 0.85 < = x < = 1, 0 < = y < 0.15, x + y + z = 1, M including one or more of Mn and Al; the coating weight of the positive electrode active material is 19-45mg / cm < 2 >, and the compaction density is 3.2-3.8 g / cm < 3 >; the negative pole piece is provided with a negative active material, the mass fraction of the silicon-based material is 20%-100%, the coating weight of the negative active material is 5-13mg / cm < 2 >, and the compaction density is 1.1-1.9 g / cm < 3 >; the amount of the electrolyte is 0.8-1.5 g / Ah, the electrolyte comprises an electrolyte solution, and the amount of the electrolyte solution outside the bare cell in the secondary battery is less than or equal to 0.1 g / Ah; the invention also relates to a corresponding electric device.
Need to check novelty before this filing date? Find Prior Art

Description

Secondary batteries and electrical devices Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery, a preparation method thereof, and an electrical device. Background Art

[0002] In recent years, as the application scope of secondary batteries has become increasingly wider, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in many fields such as power tools, electric bicycles, electric motorcycles and electric vehicles.

[0003] As secondary batteries have made great progress, higher requirements have been placed on their energy density. Therefore, seeking a secondary battery with high energy density has become one of the key areas of focus for those skilled in the art.

[0004] Summary of the Invention

[0005] The present application has been made in view of the above-mentioned problems, and one of its objects is to provide a secondary battery having a high energy density.

[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a secondary battery, comprising:

[0007] The positive electrode sheet has a positive electrode active material, and the positive electrode active material includes Li a Ni x Co y M z O2, wherein 0.2≤a≤1.2, 0.85≤x≤1, 0≤y<0.15, x+y+z=1, M includes one or more of Mn and Al; the coating weight of the positive electrode active material is 19 mg / cm 2 ~45mg / cm 2 The compaction density of the positive electrode is 3.2g / cm 3 ~3.8g / cm 3 ;

[0008] The negative electrode sheet has a negative electrode active material, the mass fraction of the silicon-based material in the negative electrode active material is 20% to 100%, and the coating weight of the negative electrode active material is 5 mg / cm 2 ~13mg / cm 2 The compaction density of the negative electrode is 1.1g / cm 3 ~1.9g / cm 3 ;and

[0009] Electrolyte: The amount of electrolyte in the secondary battery is 0.8g / Ah to 1.5g / Ah. The electrolyte includes electrolyte solution. The amount of electrolyte solution outside the bare cell of the secondary battery is ≤0.1g / Ah.

[0010] The positive and negative electrode sheets in the secondary battery of the present application adopt a higher compaction density; an extremely low total amount of electrolyte is used, and the amount of electrolyte outside the bare cell that does not contribute to the capacity is minimized; a high-nickel ternary positive electrode material, a high-silicon negative electrode active material and a larger coating weight are used; by combining the above technical means, the secondary battery can have a higher energy density.

[0011] In any embodiment, a separator is provided between the positive and negative electrode sheets, and a first superabsorbent polymer layer is provided on the surface of the separator. The superabsorbent polymer in the first superabsorbent polymer layer has an equilibrium swelling rate of 150% to 300%. This further improves the liquid retention between the separator and the electrode sheets, further concentrating the electrolyte within the bare cell and increasing the energy density of the secondary battery.

[0012] In any embodiment, a second super absorbent polymer layer is provided on the surface of the positive electrode and / or the negative electrode, and the equilibrium swelling ratio of the super absorbent polymer in the second super absorbent polymer layer is 150% to 300%. This can further improve the energy density of the secondary battery.

[0013] In any embodiment, the coating weight of the super absorbent polymer is 0.1 mg / cm 2 ~1.4mg / cm 2 In this way, the liquid retention requirements of the positive and negative electrodes can be well met.

[0014] In any embodiment, the coating weight of the super absorbent polymer is 0.1 mg / cm 2 ~1.0mg / cm 2 .

[0015] In any embodiment, the superabsorbent polymer includes one or more of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes, and polysulfate electrolytes.

[0016] In any embodiment, the electrolyte further comprises a gel electrolyte, and the mass ratio of the gel electrolyte to the electrolyte is 1:(0.05-0.4). In this way, the electrolyte can be better locked in the bare cell and the electrolyte can be reduced from being squeezed out due to the expansion of the high silicon electrode during charging.

[0017] In any embodiment, the mass ratio of the gel electrolyte to the electrolyte solution is 1:(0.05-0.25).

[0018] In any embodiment, the monomers forming the gel electrolyte include one or more of methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, n-butyl methacrylate, butyl acrylate, n-octyl methacrylate, n-octyl acrylate, vinyl acetate, vinylene carbonate, vinylethylene carbonate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, allyl methacrylate, divinylbenzene, polyvinyl alcohol and styrene.

[0019] In any embodiment, the initiator for forming the gel electrolyte includes one or more of persulfate, azo initiator, and organic peroxide initiator.

[0020] In any embodiment, the coating weight of the positive electrode active material is 25 mg / cm 2 ~35mg / cm 2 In this way, the energy density of the secondary battery can be further improved.

[0021] In any embodiment, the compacted density of the positive electrode sheet is 3.5 g / cm 3 ~3.7g / cm 3 In this way, the total amount of electrolyte required in the positive electrode film layer can be further reduced, and the energy density of the secondary battery can be further improved.

[0022] In any embodiment, the coating weight of the negative electrode active material is 7 mg / cm 2 ~10.5mg / cm 2 In this way, the energy density of the secondary battery can be further improved.

[0023] In any embodiment, the compacted density of the negative electrode sheet is 1.6 g / cm 3 ~1.8g / cm 3 In this way, the total amount of electrolyte required in the negative electrode film layer can be further reduced, and the energy density of the secondary battery can be further improved.

[0024] In any embodiment, the amount of electrolyte in the secondary battery is 0.9 g / Ah to 1.4 g / Ah. In this way, the energy density of the secondary battery is further improved while meeting the required amount of electrolyte in the pores of the positive and negative electrode sheets during charge and discharge.

[0025] In any embodiment, the mass fraction of the silicon-based material in the negative electrode active material is 40% to 100%, thereby further improving the energy density of the secondary battery.

[0026] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect of the present application.

[0027] In the secondary battery of the present application, the positive electrode and the negative electrode adopt a higher compaction density; an extremely low amount of electrolyte is used, and the amount of electrolyte outside the bare cell that does not contribute to the capacity is minimized; combined with a high-nickel ternary positive electrode material, a high-silicon negative electrode active material and a larger active material coating weight; the secondary battery can have a higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to better describe and illustrate the embodiments and / or examples of the present application, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered as limiting the scope of the disclosed application, the presently described embodiments and / or examples, and any of the best modes currently understood for these applications.

[0029] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0030] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0031] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0032] Description of reference numerals:

[0033] 5. Secondary battery; 51. Housing; 52. Electrode assembly; 53. Cover; 6. Electrical device. DETAILED DESCRIPTION

[0034] Below, the embodiments of the secondary battery and the electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0035] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values ​​and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0039] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0040] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0041] The weights described in this specification may be weight units known in the chemical industry, such as μg, mg, g, and kg.

[0042] At present, as the application scope of secondary batteries becomes wider and wider, higher requirements are also put forward for the energy density of secondary batteries. Existing high-energy-density secondary batteries usually use lithium metal negative electrodes. Due to the strong activity and poor stability of lithium metal negative electrodes, the practical application of lithium metal negative electrode high-energy-density secondary batteries is limited. Therefore, seeking a secondary battery that uses a non-lithium metal negative electrode and has a higher energy density has become one of the focuses of those skilled in the art. In this regard, the present application provides a secondary battery that does not require a lithium metal negative electrode and has a higher energy density.

[0043] In some embodiments, the first aspect of the present application provides a secondary battery, including:

[0044] The positive electrode sheet has a positive electrode active material, the positive electrode active material includes Li a Ni x Co y M z O2, wherein 0.2≤a≤1.2, 0.85≤x≤1, 0≤y<0.15, x+y+z=1, M includes one or more of Mn and Al; the coating weight of the positive electrode active material is 19 mg / cm 2 ~45mg / cm 2 The compaction density of the positive electrode is 3.2g / cm 3 ~3.8g / cm 3 ;

[0045] The negative electrode sheet has a negative electrode active material, the mass fraction of the silicon-based material in the negative electrode active material is 20% to 100%, and the coating weight of the negative electrode active material is 5 mg / cm 2 ~13mg / cm 2 The compaction density of the negative electrode is 1.1g / cm 3 ~1.9g / cm 3 ;

[0046] Electrolyte: The amount of electrolyte in the secondary battery is 0.8g / Ah to 1.5g / Ah. The electrolyte includes electrolyte solution. The amount of electrolyte solution outside the bare cell of the secondary battery is ≤0.1g / Ah.

[0047] In the secondary battery of the present application, the positive electrode and the negative electrode adopt a higher compaction density, which can reduce the electrolyte filling demand in the pores of the electrode film layer, and at the same time reduce the interface contact between the active material and the electrolyte, reduce the side reaction between the active material and the electrolyte, and reduce the total electrolyte demand; adopt an extremely low total amount of electrolyte, and try to minimize the amount of electrolyte outside the bare cell that does not contribute to the capacity; adopt high nickel ternary positive electrode material, high silicon negative electrode active material and a large coating weight; through the combination of the above technical means, the secondary battery can have a higher energy density, and its energy density can reach more than 400Wh / kg. In addition, the secondary battery does not need to use a lithium metal negative electrode with high activity and poor stability to improve the battery energy density, which can make the secondary battery have better stability.

[0048] It can be understood that the amount of electrolyte in a secondary battery includes the amount of electrolyte and the amount of gel electrolyte; wherein, the electrolyte includes the electrolyte inside the bare cell and the electrolyte outside the bare cell. Disassemble the secondary battery, take out the bare cell, and weigh the remaining electrolyte in the battery shell to obtain the amount of electrolyte outside the bare cell; disassemble the bare cell, take out the gel electrolyte and electrolyte inside it and weigh them; add the amount of gel electrolyte, the amount of electrolyte inside the bare cell and the amount of electrolyte outside the bare cell to get the amount of electrolyte in the secondary battery. The electrolyte outside the bare cell refers to the electrolyte that is free outside the bare cell, and this part of the electrolyte does not play a role in the capacity of the secondary battery; therefore, in order to improve the energy density of the secondary battery, the proportion of the electrolyte outside the bare cell in the electrolyte should be reduced as much as possible.

[0049] It should be noted that the secondary battery will be accompanied by the deintercalation and consumption of Li during the charge and discharge process, and the molar content of Li will change when the secondary battery is discharged to different states; a Ni x Co y M z The value range of a in O2 is limited to include the molar content of Li in different charge and discharge states of the secondary battery (usually the battery voltage is between 2V and 5V).

[0050] It is understood that the coating weight of the positive electrode active material in the positive electrode sheet can be but is not limited to 19 mg / cm 2 , 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 , 26mg / cm 2 , 28mg / cm2 、30mg / cm 2 、32mg / cm 2 、34mg / cm 2 、36mg / cm 2 、38mg / cm 2 , 40mg / cm 2 , 42mg / cm 2 , 44mg / cm 2 , 45mg / cm 2 The compaction density of the positive electrode sheet can be but not limited to 3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 The mass fraction of the silicon-based material in the negative electrode active material can be, but is not limited to, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 100%. The coating weight of the negative electrode active material can be, but is not limited to, 5 mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、 13mg / cm 2 The compaction density of the negative electrode sheet can be but not limited to 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3; The amount of electrolyte in the secondary battery can be but not limited to 0.8g / Ah, 0.9g / Ah, 1.0g / Ah, 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah; the amount of electrolyte outside the bare cell in the electrolyte can be but not limited to 0g / Ah, 0.01g / Ah, 0.02g / Ah, 0.03g / Ah, 0.04g / Ah, 0.05g / Ah, 0.06g / Ah, 0.07g / Ah, 0.08g / Ah, 0.09g / Ah, 0.1g / Ah.

[0051] In some embodiments, the coating weight of the positive electrode active material is 25 mg / cm 2 ~35mg / cm 2 If the coating weight of the positive electrode active material in the positive electrode sheet is too low, the proportion of active material will be reduced, and the weight proportion of the substrate, shell, auxiliary materials, etc. in the battery will be relatively increased, which will reduce the weight energy density of the battery; if the coating weight is too high, the positive electrode film layer will be too thick, making it difficult to achieve the set compaction density. The coating weight of the positive electrode active material should be controlled at 25mg / cm 2 ~35mg / cm 2 range, the energy density of the secondary battery can be further improved.

[0052] In some embodiments, the compacted density of the positive electrode sheet is 3.5 g / cm 3 ~3.7g / cm 3 In this way, the total amount of electrolyte required in the positive electrode film layer can be further reduced, and the energy density of the secondary battery can be further improved.

[0053] In some embodiments, the coating weight of the negative electrode active material in the negative electrode sheet is 7 mg / cm 2 ~10.5mg / cm 2 . The energy density of secondary batteries can be further improved.

[0054] In some embodiments, the compacted density of the negative electrode sheet is 1.6 g / cm 3 ~1.8g / cm 3 In this way, the total amount of electrolyte required in the negative electrode film layer can be further reduced, and the energy density of the secondary battery can be further improved.

[0055] In some embodiments, the amount of electrolyte in the secondary battery is 0.9 g / Ah to 1.4 g / Ah. This further reduces the total amount of electrolyte required for the positive and negative electrode membranes during charge and discharge, thereby further improving the energy density of the secondary battery.

[0056] In some embodiments, the mass fraction of the silicon-based material in the negative electrode active material is 40% to 100%. In this way, using a higher proportion of silicon-based material in the negative electrode active material can further improve the energy density of the secondary battery.

[0057] In some embodiments, the secondary battery further includes a separator disposed between the positive electrode sheet and the negative electrode sheet, with the separator and the positive electrode sheet spaced apart by 0 μm to 20 μm. By controlling the spacing between the separator and the positive electrode sheet to within 20 μm, sufficient electrolyte can be filled between the positive electrode sheet and the separator, better meeting the liquid retention requirements of the positive electrode film layer. Furthermore, the electrolyte can be primarily concentrated within the bare cell, reducing the amount of electrolyte outside the bare cell, thereby facilitating an increase in the energy density of the secondary battery.

[0058] In some embodiments, the spacing between the separator and the negative electrode plate is 0 μm to 20 μm. This allows sufficient electrolyte to be filled between the negative electrode plate and the separator, better meeting the negative electrode film layer's liquid retention requirements. It also allows the electrolyte to be further concentrated within the bare cell, further reducing the amount of electrolyte outside the bare cell, thereby further improving the energy density of the secondary battery.

[0059] In some embodiments, the spacing between the separator and the positive electrode sheet, and the spacing between the separator and the negative electrode sheet can be controlled by adjusting the winding tension when the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form an electrode assembly.

[0060] Specifically, when the distance between the electrode and the separator needs to be reduced, the tension during winding of the electrode can be appropriately increased; when the distance between the electrode and the separator needs to be increased, the tension during winding of the electrode can be appropriately reduced. When the winding tension is low, the distance between the electrode and the separator will be relatively large after winding, which can accommodate more electrolyte; however, if the winding tension is too low, the distance between the electrode and the separator will be too large, affecting the dynamics of the battery and increasing the risk of lithium plating. Therefore, it is necessary to control the magnitude of the winding tension within an appropriate range to ensure that the distance between the electrode and the separator is within the set range.

[0061] In some embodiments, a first superabsorbent polymer layer is further provided on the surface of the separator. The superabsorbent polymer in this first superabsorbent polymer layer has an equilibrium swelling ratio of 150% to 300%. Providing this superabsorbent polymer on the surface of the separator further improves the liquid retention between the separator and the electrode within the bare cell, further concentrating the electrolyte within the bare cell and reducing the amount of electrolyte outside the bare cell, thereby further increasing the energy density of the secondary battery.

[0062] In some embodiments, a second superabsorbent polymer layer is disposed on the surface of the positive and / or negative electrode sheets, and the superabsorbent polymer in this second superabsorbent polymer layer has an equilibrium swelling ratio of 150% to 300%. Similarly, by disposing the superabsorbent polymer on the surface of the positive and / or negative electrode sheets, the liquid retention capacity between the separator and the sheet within the bare cell can be further improved, further concentrating the electrolyte within the bare cell, further reducing the amount of electrolyte outside the bare cell, and thus further increasing the energy density of the secondary battery.

[0063] It can be understood that the above-mentioned highly liquid-absorbent polymer can be provided only on one side surface of the isolation membrane, can be provided on both opposite sides of the isolation membrane, can be provided only on the surface of the positive electrode plate or the negative electrode plate, can be provided on the surfaces of both the positive electrode plate and the negative electrode plate, and can also be provided on the surface of both the isolation membrane and the surface of the plate.

[0064] It should be noted that the equilibrium swelling ratio of a superabsorbent polymer can reflect its liquid-retention capacity. The equilibrium swelling ratio of a superabsorbent polymer can be calculated using the following formula: Q = Ws / Wd, where Q is the equilibrium swelling ratio of the superabsorbent polymer, Ws is the weight of the superabsorbent polymer after equilibrium swelling, and Wd is the dry weight of the superabsorbent polymer.

[0065] It can be understood that when a highly absorbent polymer comes into contact with an electrolyte solvent, the molecular chain segments between the cross-linking points of the polymer are still relatively long and have considerable flexibility, so the solvent molecules can easily penetrate into the polymer, causing the polymer volume to expand; however, the stretching of the molecular chains between the cross-linking points will reduce its conformational entropy, causing the molecular network to produce elastic contraction force, preventing the solvent molecules from entering the molecular network; when these two opposite effects offset each other, the system reaches a swelling equilibrium state, and the volume of the polymer no longer changes.

[0066] In some embodiments, the coating weight of the superabsorbent polymer is 0.1 mg / cm 2 ~1.4mg / cm 2 The coating weight of the super absorbent polymer is controlled at 0.1 mg / cm 2 ~1.4mg / cm 2 It can well meet the liquid retention requirements of the positive electrode and the negative electrode. It is understood that the coating weight of the high liquid absorption polymer can be but not limited to 0.1 mg / cm 2 , 0.2mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2, 0.6mg / cm 2 , 0.7mg / cm 2 , 0.8mg / cm 2 , 0.9mg / cm 2 , 1.0mg / cm 2 , 1.1mg / cm 2 , 1.2mg / cm 2 , 1.3mg / cm 2 , 1.4mg / cm 2 .

[0067] In some embodiments, the coating weight of the superabsorbent polymer is 0.1 mg / cm 2 ~1.0mg / cm 2 In this way, the amount of superabsorbent polymer used can be further reduced while meeting the liquid retention requirements of the positive and negative electrode sheets.

[0068] In some embodiments, a highly absorbent polymer can be dissolved in an organic solvent such as acetone, and then the polymer can be coated on the surface of the isolation membrane or the electrode by spraying, dipping, roller coating, etc., thereby forming a coating of the highly absorbent polymer on the isolation membrane or the electrode.

[0069] In some embodiments, the superabsorbent polymer includes one or more of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes, and polysulfate electrolytes.

[0070] In some embodiments, the electrolyte also includes a gel electrolyte, and the mass ratio of the gel electrolyte to the electrolyte is 1:(0.05-0.4). By using a specific content of gel electrolyte, the electrolyte's ability to retain liquid inside the bare cell and in the pores of the electrode film layer can be further enhanced, better locking the electrolyte within the bare cell and reducing the extrusion of the electrolyte due to the charging expansion of the high-silicon electrode. At the same time, combining a certain amount of liquid electrolyte can improve the electrode interface wetting and improve the capacity and other electrical properties of the gel electrolyte.

[0071] It will be appreciated that the mass ratio of the gel electrolyte to the electrolyte in the electrolyte may be, but is not limited to, 1:0.05, 1:0.08, 1:0.10, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.20, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.30, 1:0.32, 1:0.34, 1:0.36, 1:0.38, or 1:0.40.

[0072] In some embodiments, the mass ratio of the gel electrolyte to the electrolyte is 1:(0.05-0.25). This can further enhance the electrolyte's ability to retain liquid within the bare cell and in the pores of the electrode film, better locking the electrolyte within the bare cell.

[0073] In some embodiments, a certain amount of polymer monomer and initiator can be added to the electrolyte during the secondary battery filling process, and the polymer monomer can be initiated to undergo in-situ polymerization under heating conditions, thereby forming a gel electrolyte. It is understood that the content of the gel electrolyte in the electrolyte can be adjusted and controlled by adjusting the amount of polymer monomer and initiator added to the electrolyte during the filling process.

[0074] In some embodiments, the monomers forming the gel electrolyte include one or more of methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, n-butyl methacrylate, butyl acrylate, n-octyl methacrylate, n-octyl acrylate, vinyl acetate, vinylene carbonate, vinyl ethylene carbonate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, allyl methacrylate, divinylbenzene, polyvinyl alcohol, and styrene.

[0075] In some embodiments, the initiator for forming the gel electrolyte includes one or more of a persulfate, an azo initiator, and an organic peroxide initiator.

[0076] A second aspect of the present application provides an electrical device, which includes the secondary battery according to the first aspect of the present application.

[0077] The secondary battery and the electric device of the present application will be described below with reference to the accompanying drawings as appropriate.

[0078] Unless otherwise specified, the components, material types, or contents of the batteries mentioned are applicable to both lithium-ion secondary batteries and sodium-ion secondary batteries.

[0079] In one embodiment of the present application, a secondary battery is provided.

[0080] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.

[0081]

Positive electrode

[0082] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0083] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0084] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. Polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0085] In some embodiments of the present application, the positive electrode active material includes a high nickel ternary positive electrode material; the coating weight of the positive electrode active material is 19 mg / cm 2 ~45mg / cm 2 The compaction density of the positive electrode is 3.2g / cm 3 ~3.8g / cm 3 ;

[0086] In some embodiments, the weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight %, based on the total weight of the positive electrode film layer.

[0087] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight%, based on the total weight of the positive electrode film layer.

[0088] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.

[0089] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40% by mass (wt%) to 80% by weight, and the viscosity at room temperature is adjusted to 5000 mPa·s (mPa·s) to 25000 mPa·s, the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold pressing with a cold rolling mill; the compacted density of the positive electrode sheet is 3.2 g / cm3 (g / cm 3 )~3.8g / cm 3 , optional 3.5g / cm 3 ~3.7g / cm 3 .

[0090] The calculation formula of the compacted density is:

[0091] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).

[0092] The mass M of the positive electrode active material per unit area of ​​the positive electrode membrane can be obtained by weighing using a standard balance.

[0093] The thickness T of the positive electrode film can be measured using a micrometer, for example, a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode film described in this application refers to the thickness of the positive electrode film in the positive electrode sheet after cold pressing and used in battery assembly.

[0094]

Negative electrode

[0095] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0096] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0097] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver and silver alloys, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.

[0098] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art.

[0099] As an example, the negative electrode active material of a lithium-ion secondary battery includes a silicon-based material and may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used.

[0100] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.

[0101] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20% by weight, based on the total weight of the negative electrode film layer.

[0102] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). The weight ratio of the other additives in the negative electrode film layer is 0 to 15% by weight, based on the total weight of the negative electrode film layer.

[0103] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing, such as rolling, is performed to obtain a negative electrode sheet. The compacted density of the negative electrode sheet is 1.1 g / m3 (g / m 3 )~1.9g / m 3 .

[0104] The mass M of the negative electrode active material per unit area of ​​the negative electrode membrane can be obtained by weighing using a standard balance.

[0105] The thickness T of the negative electrode film can be measured using a micrometer, such as a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode film described in this application refers to the thickness of the negative electrode film after cold pressing and compaction and used in the negative electrode sheet assembled into the battery.

[0106] Electrolytes

[0107] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0108] In some embodiments, the electrolyte comprises an electrolyte solution comprising an electrolyte salt and a solvent.

[0109] In some embodiments, the electrolyte salt of the lithium ion secondary battery can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0110] The electrolyte salt of the sodium ion secondary battery can be selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.

[0111] The concentration of the electrolyte salt is generally 0.5 mol / L to 5 mol / L.

[0112] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0113] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0114] In some embodiments, the electrolyte further comprises a gel electrolyte.

[0115]

Isolation film

[0116] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0117] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0118] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may optionally be 12 μm to 20 μm.

[0119] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0120] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0121] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0122] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.

[0123] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0124] In some embodiments, the secondary batteries 5 can be assembled into a battery module. The number of secondary batteries 5 contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0125] In the battery module, the plurality of secondary batteries 5 can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 can be fixed by fasteners.

[0126] Optionally, the battery module may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0127] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0128] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.

[0129] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0130] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0131] Figure 3 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0132] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0133] The following are some examples.

[0134] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0135] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.

[0136] 1. Implementation

[0137] Example 1

[0138] 1) Preparation of positive electrode sheet

[0139] The positive electrode active material Li a Ni x Co y Mz O2, conductive agent superconducting carbon SP, and binder PVDF were mixed thoroughly in N-methylpyrrolidone solvent at a weight ratio of 98:1:1 to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet. The coating weight of the positive electrode active material was 30 mg / cm 2 The compaction density of the positive electrode is 3.5g / cm 3 Wherein, in the chemical formula of the positive electrode active material, a is 1, x is 0.92, y is 0.05, x+y+z=1, and M is Mn.

[0140] 2) Preparation of negative electrode sheet

[0141] The negative electrode active material graphite + silicon oxide, the conductive agent carbon nanotube + superconducting carbon, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) were thoroughly stirred and mixed in deionized water at a mass ratio of 94:2:3:1 to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet. The mass fraction of the silicon-based material in the negative electrode active material was 40%, and the coating weight of the negative electrode active material was 9 mg / cm 2 The compaction density of the negative electrode is 1.7g / cm 3 .

[0142] 3) Isolation film

[0143] Use polyethylene (PE) isolation film.

[0144] 4) Battery cell assembly

[0145] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound to form a bare cell, which is then placed in an outer package to produce a dry cell. During the preparation of the bare cell, the spacing between the positive electrode sheet and separator is adjusted to 20μm, and the spacing between the negative electrode sheet and separator is adjusted to 20μm by controlling the tension during the winding of the electrode sheets.

[0146] 5) Injection

[0147] The dry cells were injected with electrolyte in two separate steps, with the mass ratio of the first injection to the second injection being 9:1. The electrolyte raw material components for the first injection were: electrolyte mother liquor, monomer, and initiator, with a mass ratio of 94.5:5:0.5. The organic solvent for the electrolyte mother liquor was a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC); the volume ratio of EC, EMC, and DEC was 20:20:60. The lithium salt of the electrolyte mother liquor was LiPF6 at a concentration of 1 mol / L. The monomer was ethylene glycol dimethacrylate, and the initiator was azobis(ethylbutyronitrile) (AIBN).

[0148] The secondary injection electrolyte consists solely of the mother electrolyte solution. After the primary injection, the cells are vacuum-sealed, left to soak, and heated to polymerize the polymer monomers in the electrolyte raw material to form a gel electrolyte, which is then injected with the secondary injection mother electrolyte solution. The total electrolyte content of the cell is 1.3g / Ah. After heating and polymerization, the mass ratio of gel electrolyte to liquid electrolyte is 1:0.11, and the amount of electrolyte present outside the bare cell is 0.05g / Ah.

[0149] Example 2

[0150] This embodiment is basically the same as embodiment 1, except that the high nickel ternary positive electrode material is different and the coating weight of the positive electrode active material is different. The chemical formula of the high nickel ternary positive electrode material in this embodiment is Li a Ni x Co y M z O2, where a is 1, x is 0.9, y is 0.05, x+y+z=1, and M is Mn; the coating weight of the positive electrode active material is 30.5 mg / cm 2 .

[0151] Example 3

[0152] This embodiment is basically the same as embodiment 1, except that the coating weight of the positive electrode active material in the positive electrode sheet is different, and the coating weight of the negative electrode active material in the negative electrode sheet is different. The coating weight of the positive electrode active material in this embodiment is 25 mg / cm 2 The coating weight of the negative electrode active material is 7.5 mg / cm 2 .

[0153] Example 4

[0154] This embodiment is basically the same as embodiment 1, except that the coating weight of the positive electrode active material in the positive electrode sheet is different, and the coating weight of the negative electrode active material in the negative electrode sheet is different. The coating weight of the positive electrode active material in this embodiment is 35 mg / cm 2 The coating weight of the negative electrode active material is 10.5 mg / cm 2 .

[0155] Example 5

[0156] This embodiment is basically the same as embodiment 1, except that the coating weight of the positive electrode active material in the positive electrode sheet is different, and the coating weight of the negative electrode active material in the negative electrode sheet is different. The coating weight of the positive electrode active material in this embodiment is 40 mg / cm 2 The coating weight of the negative electrode active material is 12 mg / cm 2 .

[0157] Example 6

[0158] This embodiment is basically the same as embodiment 1, except that the compaction density of the positive electrode sheet is different. The compaction density of the positive electrode sheet in this embodiment is 3.7 g / cm 3 .

[0159] Example 7

[0160] This embodiment is basically the same as embodiment 1, except that the compaction density of the positive electrode sheet is different. The compaction density of the positive electrode sheet in this embodiment is 3.8 g / cm 3 .

[0161] Example 8

[0162] This embodiment is basically the same as embodiment 1, except that the coating weight of the negative electrode active material in the negative electrode sheet is different. The coating weight of the negative electrode active material in this embodiment is 13 mg / cm 2 .

[0163] Example 9

[0164] This embodiment is basically the same as embodiment 1, except that the compaction density of the negative electrode sheet is different. The compaction density of the negative electrode sheet in this embodiment is 1.6 g / cm 3 .

[0165] Example 10

[0166] This embodiment is basically the same as embodiment 1, except that the compaction density of the negative electrode sheet is different. The compaction density of the negative electrode sheet in this embodiment is 1.8 g / cm 3 .

[0167] Example 11

[0168] This embodiment is substantially the same as embodiment 1, with the only difference being the amount of electrolyte in the secondary battery, which is 0.9 g / Ah.

[0169] Example 12

[0170] This embodiment is substantially the same as embodiment 1, with the only difference being the amount of electrolyte in the secondary battery, which is 1.4 g / Ah.

[0171] Example 13

[0172] This embodiment is substantially the same as embodiment 1, differing only in the amount of electrolyte in the secondary battery and the amount of electrolyte solution outside the bare cell. In this embodiment, the amount of electrolyte is 1.35 g / Ah, and the amount of electrolyte solution outside the bare cell is 0.1 g / Ah.

[0173] Example 14

[0174] This embodiment is basically the same as the embodiment 1, except that: in this embodiment, polycarbonate diol superabsorbent polymer is coated on both the positive electrode and the negative electrode, and the coating weight of the superabsorbent polymer on the positive electrode is 0.5 mg / cm 2 The coating weight of the super absorbent polymer on the negative electrode is 0.5 mg / cm 2 The equilibrium liquid absorption rate of the super absorbent polymer is 200%.

[0175] Example 15

[0176] This embodiment is substantially the same as embodiment 1, with the only difference being the distance between the separator and the positive electrode plate. In this embodiment, the distance between the separator and the positive electrode plate is 20 μm.

[0177] Example 16

[0178] This embodiment is substantially the same as embodiment 1, with the only difference being the distance between the separator and the negative electrode plate. In this embodiment, the distance between the separator and the negative electrode plate is 20 μm.

[0179] Example 17

[0180] This embodiment is basically the same as embodiment 1, except that in this embodiment, a super absorbent polymer is coated on the surface of the isolation membrane, the equilibrium swelling rate of the super absorbent polymer is 200%, and the coating weight of the super absorbent polymer is 0.5 mg / cm 2 .

[0181] Example 18

[0182] This embodiment is basically the same as embodiment 17, except that the coating weight of the super absorbent polymer on the isolation membrane surface is different. In this embodiment, the coating weight of the super absorbent polymer on the isolation membrane surface is 1 mg / cm 2 .

[0183] Example 19

[0184] This embodiment is basically the same as embodiment 17, except that the coating weight of the super absorbent polymer on the surface of the isolation membrane is different. In this embodiment, the coating weight of the super absorbent polymer on the surface of the isolation membrane is 1.4 mg / cm 2 .

[0185] Example 20

[0186] This embodiment is substantially the same as embodiment 1, with the only difference being that the mass ratio of the gel electrolyte to the free liquid electrolyte in the electrolyte after heating and polymerization is different. In this embodiment, the mass ratio of the gel electrolyte to the free liquid electrolyte in the electrolyte after heating and polymerization is 1:0.25.

[0187] 2. Comparative Example

[0188] Comparative Example 1

[0189] This comparative example is basically the same as Example 1, except that the positive electrode active material used in the comparative example 1 is different. The positive electrode active material used in the positive electrode sheet in the comparative example 1 is a high nickel ternary positive electrode material with the chemical formula of Li a Ni x Co y M z O2, wherein a is 1, x is 0.8, y is 0.1, x+y+z=1, and M is Mn.

[0190] Comparative Example 2

[0191] This comparative example is basically the same as Example 1, except that the coating weight of the positive electrode active material in the positive electrode sheet is different. The coating weight of the positive electrode active material in the positive electrode sheet in Comparative Example 2 is 15 mg / cm 2 .

[0192] Comparative Example 3

[0193] This comparative example is basically the same as Example 1, except that the compaction density of the positive electrode sheet is different. The compaction density of the positive electrode sheet in Comparative Example 3 is 3.1 g / cm 3 .

[0194] Comparative Example 4

[0195] This comparative example is substantially the same as Example 1, with the only difference being that the negative electrode active material in the negative electrode sheet is different. In Comparative Example 4, the negative electrode active material is graphite:silicon oxide = 95:5.

[0196] Comparative Example 5

[0197] This comparative example is basically the same as Example 1, except that the coating weight of the negative electrode active material in the negative electrode sheet is different. The coating weight of the negative electrode active material in the negative electrode sheet in Comparative Example 5 is 15 mg / cm 2 .

[0198] Comparative Example 6

[0199] This comparative example is basically the same as Example 1, except that the compaction density of the negative electrode sheet is different. The compaction density of the negative electrode sheet in Comparative Example 6 is 1.0 g / cm 3 .

[0200] Comparative Example 7

[0201] This comparative example is substantially the same as Example 1, except that the amount of electrolyte in the battery cell is different. The amount of electrolyte in the battery cell of Comparative Example 7 is 1.6 g / Ah.

[0202] Comparative Example 8

[0203] This comparative example is substantially the same as Example 1, except that the amount of electrolyte outside the bare cell is different. In this comparative example 8, the amount of electrolyte outside the bare cell is 0.2 g / Ah.

[0204] Comparative Example 9

[0205] This comparative example is essentially the same as Example 1, differing only in the mass ratio of the gel electrolyte to the liquid electrolyte in the electrolyte after heat polymerization. In this example, the mass ratio of the gel electrolyte to the liquid electrolyte in the electrolyte after heat polymerization is 1:0, meaning that no liquid electrolyte is contained.

[0206] 3. Test Method

[0207] 1) Test of electrolyte volume outside the bare cell

[0208] Remove the bare battery cell and weigh the remaining electrolyte in the shell.

[0209] 2) Test of the distance between the isolation film and the electrode

[0210] X-Ray CT is used to photograph and measure the distance between the isolation membrane and the pole piece.

[0211] 3) Gel electrolyte and electrolyte mass ratio test

[0212] The bare cell is retrieved and centrifuged to obtain the free liquid electrolyte in the bare cell, which is then combined with the remaining electrolyte in the shell and weighed to obtain the weight of the liquid electrolyte; the gel electrolyte on the bare cell is scraped off and weighed, and the part that cannot be scraped off is used to perform auxiliary calibration test on the mass of the gel electrolyte using a TG-MS thermogravimetric analyzer.

[0213] 4) Equilibrium swelling rate test of highly absorbent polymers

[0214] The dried polymer sample is weighed to obtain the dry weight Wd of the polymer;

[0215] The polymer was immersed in an electrolyte at room temperature for 24 hours, then taken out of the electrolyte, and the electrolyte on the surface was removed with filter paper and weighed to obtain the weight Ws of the polymer after swelling equilibrium; wherein the electrolyte includes a solvent and a lithium salt; the solvent is a mixed solvent formed by EC, EMC and DEC in a volume ratio of 20:20:60; the lithium salt is LiPF6 with a concentration of 1 mol / L;

[0216] The equilibrium swelling ratio of the polymer is calculated by the following formula: Q = Ws / Wd.

[0217] 5) Mass Energy Density (GED) test

[0218] Measure the weight of the battery cell and record it as M;

[0219] At 25°C, charge the battery at a constant current rate of 1 / 3C to 4.25V, then switch to constant voltage charging until the current drops to 0.05C, then discharge the battery at a constant current rate of 1 / 3C to 2.5V, and record the discharge energy value ED.

[0220] GED=ED / M, unit is Wh / kg.

[0221] The parameters and performance test data of the secondary batteries of the above embodiments and comparative examples are shown in Table 1, Table 2 and Table 3.

[0222] Table 1

[0223] Table 2

[0224] Table 3

[0225] From the data in the table we can see that:

[0226] It can be seen from Comparative Example 1 and Examples 1 and 2 that a higher Ni content in the positive electrode material is conducive to obtaining a higher energy density.

[0227] From Comparative Example 2 and Examples 1, 3 to 5, it can be seen that the coating weight is 35 mg / cm 2 When the coating weight is below , the greater the coating weight, the greater the proportion of active material in the total weight of the battery cell, and the higher the weight energy density can be obtained. However, when the coating weight is further increased, the diffusion impedance of the thick electrode deteriorates seriously, the capacity of the battery cell is lost, and the weight energy density decreases instead of increases.

[0228] As can be seen from Comparative Example 3 and Examples 6 and 7, the greater the density of the positive electrode, the more layers of active material can be packed into the same housing, thereby increasing the weight energy density of the battery cell. However, excessive density can damage the active material particle structure and cause capacity loss, so it should not be too high.

[0229] As can be seen from Comparative Example 4, the mass proportion of silicon-based materials in the negative electrode decreases, and the weight energy density decreases. As can be seen from Comparative Example 5 and Example 8, under the same positive electrode coating weight, if the negative electrode coating weight is too small, the problem of negative electrode lithium plating will occur, resulting in capacity loss; when the negative electrode coating weight is too large, there will be more ineffective negative electrode active material, which will reduce the weight energy density. Therefore, the negative electrode coating weight needs to be within an appropriate range.

[0230] It can be seen from Comparative Example 6 and Examples 9 and 10 that the greater the negative electrode density, the higher the weight energy density of the battery cell; however, excessive density will destroy the active material particle structure and cause capacity loss, so the negative electrode density cannot be too large and needs to be within an appropriate range.

[0231] As can be seen from Comparative Example 7 and Examples 11 and 12, the higher the total electrolyte content of the cell, the more electrolyte will be free outside the bare cell, which will not help the capacity development and reduce the weight energy density. The lower the total electrolyte content, the higher the weight energy density, but too low an electrolyte content will lead to a loss of capacity development. Therefore, the electrolyte content must also be controlled within the range specified in the claims.

[0232] It can be seen from Comparative Example 8 and Examples 1 and 13 that, under the same total electrolyte amount, the higher the free electrolyte outside the bare cell, the more unfavorable it is for the normal performance of the cell capacity, resulting in a loss of the cell's weight energy density.

[0233] It can be seen from Examples 1, 14, 17 to 19 that after coating the surface of the positive and negative electrodes or the surface of the diaphragm with a highly absorbent polymer, the free electrolyte outside the bare cell can be reduced at the same electrolyte amount, thereby reducing capacity loss and being more conducive to obtaining a higher weight energy density.

[0234] It can be seen from Examples 1, 15, and 16 that by appropriately adjusting the gap between the positive and negative electrode sheets and the separator, the external free electrolyte can also be reduced to obtain a higher weight energy density.

[0235] It can be seen from Comparative Example 9 and Examples 1 and 20 that the gel electrolyte combined with an appropriate amount of liquid electrolyte can improve electrode wetting and capacity utilization, and obtain a higher weight energy density; however, under the same total amount of electrolyte, the higher the specific gravity of the liquid electrolyte, the more ineffective electrolyte will be released outside the bare cell, which is not conducive to capacity utilization.

[0236] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, include: A positive electrode sheet having a positive electrode active material, wherein the positive electrode active material includes Li a Ni x Co y M z O 2 , wherein 0.2≤a≤1.2, 0.85≤x≤1, 0≤y<0.15, x+y+z=1, M includes one or more of Mn and Al; the coating weight of the positive electrode active material is 19 mg / cm 2 ~45mg / cm 2 The compaction density of the positive electrode sheet is 3.2 g / cm 3 ~3.8g / cm 3 ; A negative electrode sheet, wherein the negative electrode sheet has a negative electrode active material, the mass fraction of the silicon-based material in the negative electrode active material is 20% to 100%, and the coating weight of the negative electrode active material is 5 mg / cm 2 ~13mg / cm 2 The compaction density of the negative electrode sheet is 1.1 g / cm 3 ~1.9g / cm 3 ;and Electrolyte, the amount of the electrolyte in the secondary battery is 0.8g / Ah to 1.5g / Ah, the electrolyte includes an electrolyte solution, and the amount of the electrolyte solution outside the bare cell of the secondary battery is ≤0.1g / Ah.

2. The secondary battery according to claim 1, It is characterized in that A separator is arranged between the positive electrode sheet and the negative electrode sheet, a first highly liquid-absorbent polymer layer is arranged on the surface of the separator, and a balanced swelling rate of the highly liquid-absorbent polymer in the first highly liquid-absorbent polymer layer is 150% to 300%.

3. The secondary battery according to claim 1 or 2, It is characterized in that A second highly liquid-absorbent polymer layer is provided on the surface of the positive electrode plate and / or the negative electrode plate, and the equilibrium swelling rate of the highly liquid-absorbent polymer in the second highly liquid-absorbent polymer layer is 150% to 300%.

4. The secondary battery according to claim 2 or 3, It is characterized in that The coating weight of the highly liquid-absorbent polymer is 0.1 mg / cm 2 ~1.4mg / cm 2 ; Optionally, the coating weight of the highly liquid-absorbent polymer is 0.1 mg / cm 2 ~1.0mg / cm 2 .

5. The secondary battery according to any one of claims 2 to 4, It is characterized in that The highly liquid-absorbent polymer includes one or more of polyacrylate electrolytes, polyether electrolytes, polycarbonate electrolytes, polycarboxylate electrolytes, silicon-based electrolytes, polythiol electrolytes, maleic anhydride electrolytes and polysulfate electrolytes.

6. The secondary battery according to any one of claims 1 to 5, It is characterized in that The electrolyte further comprises a gel electrolyte, wherein the mass ratio of the gel electrolyte to the electrolyte is 1:(0.05-0.4); Optionally, the mass ratio of the gel electrolyte to the electrolyte is 1:(0.05-0.25).

7. The secondary battery according to claim 6, It is characterized in that The monomers forming the gel electrolyte include one or more of methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, n-butyl methacrylate, butyl acrylate, n-octyl methacrylate, n-octyl acrylate, vinyl acetate, vinylene carbonate, vinylethylene carbonate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, allyl methacrylate, divinylbenzene, polyvinyl alcohol and styrene.

8. The secondary battery according to claim 6 or 7, It is characterized in that The initiator for forming the gel electrolyte includes one or more of persulfate, azo initiator and organic peroxide initiator.

9. The secondary battery according to any one of claims 1 to 8, It is characterized in that The coating weight of the positive electrode active material is 25 mg / cm 2 ~35mg / cm 2 .

10. The secondary battery according to any one of claims 1 to 9, It is characterized in that The compaction density of the positive electrode sheet is 3.5 g / cm 3 ~3.7g / cm 3 .

11. The secondary battery according to any one of claims 1 to 10, It is characterized in that The coating weight of the negative electrode active material is 7 mg / cm 2 ~10.5mg / cm 2 .

12. The secondary battery according to any one of claims 1 to 11, It is characterized in that The compaction density of the negative electrode plate is 1.6 g / cm 3 ~1.8g / cm 3 .

13. The secondary battery according to any one of claims 1 to 12, It is characterized in that The amount of the electrolyte in the secondary battery is 0.9 g / Ah to 1.4 g / Ah.

14. The secondary battery according to any one of claims 1 to 13, It is characterized in that The mass fraction of the silicon-based material in the negative electrode active material is 40% to 100%.

15. An electrical device comprising the secondary battery according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Water-based ceramic coating for lithium ion battery and application thereof

    CN103102717A

  • Lithium ion battery

    CN106602131A

  • Lithium ion battery

    CN111416145A

  • Lithium ion secondary battery and electric device

    CN115020789A

  • Lithium-ion secondary cell

    WO2014178113A1

Cited By

  • Negative pole piece and secondary battery

    CN120914198A